Unveiling the Role of Psychological Factors in Adult Learners’ English Language Development - I Putu Edi Sutrisna; I Gusti Ayu Putu Novita Sari Paragae; Anak Agung Gede Mahendra Kusuma (LUNAR, 2026)
This study explores the psychological factors influencing the English language development of adult learners in Pakisan Village, a rural community preparing for community-based tourism. Using an Interpretative Phenomenological Analysis (IPA) approach, the research examines how ten adult learners aged 30–50 interpreted their experiences of motivation, anxiety, confidence, and psychological empowerment while participating in a short English course. Data were collected through in-depth interviews and classroom observations. The findings reveal that learners’ motivation was initially driven by instrumental needs related to tourism but gradually shifted toward intrinsic interest as they experienced competence and enjoyment. Anxiety shaped by age, educational history, and fear of making mistakes, initially hindered participation but decreased through shared struggles, peer support, and positive classroom interactions. Confidence developed slowly as learners accumulated successful learning moments, enabling them to take risks and communicate more willingly. Notably, the study found evidence of psychological empowerment, as learners began to view themselves as capable of engaging with tourists and contributing to the village’s tourism development. These psychological processes collectively shaped learners’ readiness to use English in real-world tourism contexts. The study concludes that emotional and psychological experiences play a central role in adult English learning in rural settings, suggesting that community-based language programs must attend to learners’ psychological needs to support sustainable language development and tourism participation.